Performing arts & Ethnicity: Sinhalese and Tamil ethnicity influences the performing arts and the artiste’s practice in Sri Lanka - Sanjeewa, Winojith (Technium Social Sciences Journal, 2021)
This paper describes how far Sinhalese and Tamil ethnicity influences the performing arts and the artiste’s practice. Here a further description will be given about the particular changes that took place regarding ethnicity during the pre-colonial, colonial and post-colonial periods and how such changes affected the artiste. Attention is paid to the separate establishment of ethnic groups such as Sinhalese and Tamil across the plantation economy during the British colonial period and how the Sinhalese-Tamil political divisions influenced the artiste and the arts.